Pemikiran KH. Hasyim Asy’ari Tentang Pendidikan Karakter dan Relevansinya Dengan Kurikulum Merdeka Belajar: Kajian Kitab Adabul Alim Wal Muta’allim - Febrianingsih, Dian; Karimah, Fakarotul; Masduki, Moh (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The aim of this research is to explain the concept of character education according to KH Hasyim Asy'ari, explain KH Hasyim Asy'ari's thoughts on student character in education and explain the relevance of KH Hasyim Asy'ari's thoughts on character education to the implementation of the 2023 Merdeka Belajar curriculum. The approach used in this research is a historical approach. With this approach, the author can use it to study the biography and works of KH Hasyim Asy'ari. The type of research that the author uses is library research, namely research carried out to solve problems which basically relies on a critical and in-depth review of relevant library materials. The limitations of the problem that will be discussed are only regarding the relevance of character education according to KH Hasyim Asy'ari and character education in the independent learning curriculum. The results of this research are that the concept of character education according to KH Hasyim Asy'ari's thoughts includes Sincerity, Practicing Qona'ah, Tawdhu', Zuhud, Behaving Waro', Behaving Patience, Avoiding Immorality and Dirty Things. The character education of students according to the thoughts of KH Hasyim Asy'ari in the book adabulalim walmuta'alim is as follows: Student Character towards Themselves, Student Character towards their Teachers, Student Character towards the lesson, Student Character towards the book (book) and learning tools. The relevance of the adabulalim walmuta'alim book to the implementation of education in 2023 includes: Faith, Devotion to God Almighty, Noble Character, Independence, Mutual Cooperation, Critical Reasoning, Creative.